Images of women ([Montreal] National Film Board of Canada)
A film about working women which reveals their attitudes about work, training and their personal roles.
1. Careers and cradles (excerpt) 2. Women at war (excerpt) 3. Service in the sky (excerpt) 4. Attention Women at work (excerpt) 5. Thin dreams (excerpt) 6. No way! not me! (excerpt) 7. Not a love story; a film about pornography (excerpt).
Keywords: Women -- Employment; Sociology